Cutaneous adverse drug reaction in a dog associated with imepitoin. Issue 2 (22nd January 2016) - Royaux, Emilie; Bhatti, Sofie; De Cock, Hilde; Van Ham, Luc; Kitshoff, Adriaan; Vandenabeele, Sophie
Abstract : Background: The macroscopic appearance of cutaneous adverse drug reactions can be similar to a plethora of skin diseases and in particular may resemble autoimmune and immune‐mediated disorders. The reaction can occur after single or multiple administrations, with the latter varying in durations of up to years of treatment. These reactions are mostly self‐limiting with cessation of the offending drug. Objectives: To report a cutaneous adverse drug reaction associated with chronic administration of imepitoin. Case report: A 4‐year‐old, Jack Russell terrier dog was presented with progressive skin lesions of 1‐week duration. The dog had a 6 month history of idiopathic epilepsy treated with imepitoin for the previous 5 months. Imepitoin is an anti‐epileptic drug that acts as a low‐affinity partial agonist of the benzodiazepine site at the GABAA receptor. The dosage of imepitoin was increased from 20 mg/kg twice daily to 30 mg/kg twice daily, 3 days before the onset of skin lesions, due to uncontrolled seizures. [Correction added on 15 February 2016 after first online publication: In the preceding sentence, the dosage of imepitoin was previously incorrect and has been amended in this current version.] Dermatological examination revealed erythema and exfoliation at the mucocutaneous junctions of the lips, lip folds, philtrum, ears, axillae and the ventral abdomen. Small erosions and depigmentation were visible on the oral mucosa, lip folds and philtrum. Histopathology was supportive of a lupoid drug reaction. Complete resolution of skin lesions was seen after discontinuation of imepitoin and low dose of prednisolone during a period of 4 weeks. No recrudescence of skin lesions was observed during a 6 month follow‐up period. Conclusion and clinical importance: Imepitoin may result in cutaneous adverse drug reactions in dogs. Abstract : Background – The macroscopic appearance of cutaneous adverse drug reactions can be similar to a plethora of skin diseases and in particular may resemble autoimmune and immune‐mediated disorders. The reaction can occur after single or multiple administrations, with the latter varying in durations of up to years of treatment. These reactions are mostly self‐limiting with cessation of the offending drug.Objectives – To report a cutaneous adverse drug reaction associated with chronic administration of imepitoin.Conclusion and clinical importance – Imepitoin may result in cutaneous adverse drug reactions in dogs.